Social Responsibility Indicators in the Stakeholders’ Perspective - Seibert, Rosane Maria; Macagnan, Clea Beatriz (Journal of Information Systems and Technology Management, 2019)
The objective of this research was identify what social responsibility information is of the stakeholder interest for the disclosure of a philanthropic higher education organization - PHEO. The exploratory inductive study was developed with application of form elaborated with the main social responsibility categories, through meetings with groups the main stakeholders. The content analysis and triangulation of the evidences identified the indicators. The research identified 169 indicators, of these, 69 are news. Some of the new indicators are specific to the organization type under study, confirming the need to observe the specific stakeholders’ interests.